Serum Enzyme Activity in Murrah Buffalo under Hot-Humid and Cold Seasonal Conditions - Singh, Mohan; Gupta, Barkha; Mittal, Pavan Kumar; Gottam, Govind Sahay; Saini , Bhagat Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was conducted to evaluate the effect of seasonal variation, specifically the hot-humid (June to September) and cold period (December to February), on selected serum enzyme activity in adult female Murrah buffalo (n=10). Blood samples were aseptically collected from the jugular vein, and serum was separated for biochemical analysis. Hepatic enzyme activities were quantified using an automated Turbo Chem 100 blood biochemistry analyzer. Seasonal variation had no significant effect on serum levels of alanine aminotransferase (ALT), lactate dehydrogenase (LDH), or alkaline phosphatase (ALP). However, aspartate amino-transferase (AST) concentrations showed a highly significant decrease (p<0.01) during the cold season. These findings suggest that while most serum enzyme levels remain relatively stable across seasonal conditions, AST is sensitive to ambient temperature changes and may serve as a potential indicator of thermal stress in Murrah buffaloes.